Predictors of mammographic microcalcifications. Issue 5 (25th September 2020) - Azam, Shadi; Eriksson, Mikael; Sjölander, Arvid; Gabrielson, Marike; Hellgren, Roxanna; Czene, Kamila; Hall, Per
Abstract: We examined the association between established risk factors for breast cancer and microcalcification clusters and their asymmetry. A cohort study of 53 273 Swedish women aged 30 to 80 years, with comprehensive information on breast cancer risk factors and mammograms, was conducted. Total number of microcalcification clusters and the average mammographic density area were measured using a Computer Aided Detection system and the STRATUS method, respectively. A polygenic risk score for breast cancer, including 313 single nucleotide polymorphisms, was calculated for those women genotyped (N = 7387). Odds ratios (ORs) and 95% confidence intervals (CIs), with adjustment for potential confounders, were estimated. Age was strongly associated with microcalcification clusters. Both high mammographic density (>40 cm 2 ), and high polygenic risk score (80‐100 percentile) were associated with microcalcification clusters, OR = 2.08 (95% CI = 1.93‐2.25) and OR = 1.22 (95% CI = 1.06‐1.48), respectively. Among reproductive risk factors, life‐time breastfeeding duration >1 year was associated with microcalcification clusters OR = 1.22 (95% CI = 1.03‐1.46). The association was confined to postmenopausal women. Among lifestyle risk factors, women with a body mass index ≥30 kg/m 2 had the lowest risk of microcalcification clusters OR = 0.79 (95% CI = 0.73‐0.85) and the association was stronger among premenopausal women. Our results suggest that age, mammographic density, genetic predictors of breast cancer, having more than two children, longer duration of breast‐feeding are significantly associated with increased risk of microcalcification clusters. However, most lifestyle risk factors for breast cancer seem to protect against presence of microcalcification clusters. More research is needed to study biological mechanisms behind microcalcifications formation. Abstract : What's new? Mammographic microcalcifications are one of the earliest mammographic signs of breast cancer. However, little is known on the predictors of mammographic microcalcifications and the mechanisms behind their formation. This large population‐based cohort study explored the association between established breast cancer risk factors and the risk of mammographic microcalcifications among pre‐ and postmenopausal women using an FDA‐approved method for detection of suspicious microcalcifications. The findings suggest that most established risk factors for breast cancer, with exception of age, mammographic density, familial history, polygenic risk score of breast cancer, having more children, and longer duration of breast‐feeding are protective against microcalcification clusters.